Pengembangan E-Modul Bangun Datar Berbasis Teori Multiple Intelligence untuk Siswa Kelas IV SDN Ngupasan - Kusuma Ardi Wijaya; Mujiyem Sapti; Rintis Rizkia Pangestika (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
The rapid development of technology has invaded the world of education over time. This, of course, must be balanced with the quality and professionalism of teachers. Teachers must be rich in information and technology mastery to build mature learning concepts. Of course, in order to generate student activity in learning, it also needs to be supported by learning tools that the teacher has prepared. The current pandemic condition makes students study online. In such conditions, teaching materials are needed to help students master the material independently. Electronic modules can be developed and integrated with the theory of multiple intelligences in learning  to build students' concepts and thinking skills in learning maximally. The results of the multiple intelligence-based e-module research developed are feasible to use because they meet the valid, practical, and effective criteria. Based on the validity test conducted by media experts, material experts, and teachers, the average score was 3.85. The practicality test through a student response questionnaire conducted with a limited and wide-field trial obtained an average score of 3.64 and was categorized as effective in learning completeness with 84%.